Capital Formation in the USSR, 1959-1974: An Econometric Investigation of Bureaucratic Intervention in the Process of Capital Construction - Green, Donald W. (The Review of Economics and Statistics, 1978)
Donald W. Green, Capital Formation in the USSR, 1959-1974: An Econometric Investigation of Bureaucratic Intervention in the Process of Capital Construction, The Review of Economics and Statistics, Vol. 60, No. 1 (Feb., 1978), pp. 39-46